2017
DOI: 10.3390/ijerph14040417
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Results of a Synthetic Intervention Model for the Primary Prevention of T2D among Elderly Individuals with Prediabetes in Rural China

Abstract: Objective: The objective of this study was to evaluate the effectiveness of a synthetic intervention model aimed at preventing type 2 diabetes and controlling plasma glucose, body weight and waist circumference in elderly individuals with prediabetes in rural China. Methods: We randomly assigned 434 (180 men and 254 women; mean age, 69 years; mean body mass index, 23.6 kg/m2) with prediabetes to either the intervention group or the control group. Each participant in the intervention group received synthetic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…We included six randomized controlled trials published between 2010 and 2017: three trials conducted in India [66–68], one in China [69], one in Brazil [70], and one in Vietnam [71]. Details of the methods, participants, intervention, comparison group, and outcome measures for each included trial are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included six randomized controlled trials published between 2010 and 2017: three trials conducted in India [66–68], one in China [69], one in Brazil [70], and one in Vietnam [71]. Details of the methods, participants, intervention, comparison group, and outcome measures for each included trial are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the methods, participants, intervention, comparison group, and outcome measures for each included trial are provided in Table 1. The randomization unit for four trials was the individual participants; two trials [68, 69] used the cluster randomization method. Of these two cluster RCTs, one study [68] pointed out that the result had been adjusted for clustering effect but did not mention the intraclass correlation coefficient (ICC) value, while the other [69] adjusted the results for age, sex, and other characteristics, but did not report applying adjustment aimed at the clustering effect.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] The Finnish Diabetes Prevention Study (DPS) reported that the cumulative incidence of diabetes was 11% in the intervention group and 23% in the control group after 4 years’ lifestyle intervention for IGT. [ 24 ] Hu et al [ 25 ] assigned 434 with prediabetes to either the intervention group or the control group, and participants in the intervention group received synthetic intervention for 1 year. They found that the incidence of diabetes was 4.2% in the intervention group, while the incidence of diabetes was 19.7% in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based primordial prevention strategies are applicable in this stage. Primary prevention strategies are indicated for these individuals, such as structured lifestyle modifications resulting in weight loss and enhanced physical fitness, that improve metabolic and CVD risk factors and prevent progression to Stage 3 DBCD, or T2D (47,(120)(121)(122)(123)(124)(125)(126)(127). At present, prediabetes is still considered as a predisease, but with further scientific delineation, prediabetes may eventually meet criteria for a true disease state.…”
Section: The Specific Context Of Dbcd As the Insulin Resistance-predimentioning
confidence: 99%